2007
DOI: 10.1021/nl062483w
|View full text |Cite
|
Sign up to set email alerts
|

Single Quantum Dot Nanowire LEDs

Abstract: We report reproducible fabrication of InP-InAsP nanowire light emitting diodes in which electron-hole recombination is restricted to a quantum-dot-sized InAsP section. The nanowire geometry naturally self-aligns the quantum dot with the n-InP and p-InP ends of the wire, making these devices promising candidates for electrically-driven quantum optics experiments. We have investigated the operation of these nano-LEDs with a consistent series of experiments at room temperature and at 10 K, demonstrating the poten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
325
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(339 citation statements)
references
References 29 publications
12
325
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] The integration of QDs in one-dimensional crystals (nanowires, NWs) has increasingly gained interest because of the improvement in the photon extraction efficiency and overall functionality. [10][11][12][13][14][15][16][17][18][19] Recently, it has been shown that self-segregation processes in ternary Al x Ga 1Àx As shells lead to the observation of luminescence stemming from 3D confined excitons. Several high-resolution imaging methods have demonstrated that the Al x Ga 1Àx As shells are indeed not homogeneous and contain nanoscale Ga-rich islands.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The integration of QDs in one-dimensional crystals (nanowires, NWs) has increasingly gained interest because of the improvement in the photon extraction efficiency and overall functionality. [10][11][12][13][14][15][16][17][18][19] Recently, it has been shown that self-segregation processes in ternary Al x Ga 1Àx As shells lead to the observation of luminescence stemming from 3D confined excitons. Several high-resolution imaging methods have demonstrated that the Al x Ga 1Àx As shells are indeed not homogeneous and contain nanoscale Ga-rich islands.…”
mentioning
confidence: 99%
“…Prior to the work presented here, we have shown that a single InAsP quantum dot grown in an InP nanowire geometry is optically active, exhibits narrow emission lines, spin polarization memory effects, 10 and can be embedded in a LED device geometry. 11 Furthermore, it is predicted that NW-QDs are ideal sources of entangled photons due to the nanowire symmetry. 12 Recently, an electron spin-to-charge conversion read-out scheme has been proposed, 13 which is compatible with controlled storage of carriers up to microseconds.…”
mentioning
confidence: 99%
“…Nanowire Growth and Device Fabrication. The nanowire quantum dots were grown in the vaporliquid-solid mode 28 by means of metal-organic vaporphase epitaxy in a similar manner as reported by Minot et al 11 Colloidal Au particles of 20 nm diameter were used to first grow an InP section for 20 min (∼2 µm) followed by 1 s of InAsP growth. The ∼4 µm long nanowires were completed by another 20 min of InP growth.…”
mentioning
confidence: 99%
“…[12][13][14] Semiconductor nanowires have been intensively studied due to their great potential for nanoscale electronics and photonics. 4,15 The growth of III-V nanowires using a metal (usually gold) as a catalyst is commonly explained within the vapor-liquid-solid (VLS) mechanism. 16 For a long time chemical vapor deposition (CVD) or chemical beam epitaxy (CBE) were the common techniques used.…”
mentioning
confidence: 99%